Effect of magnetized mixing water on the fresh and hardened state properties of steel fibre reinforced self-compacting concrete - Ghorbani, Saeid; Sharifi, Sohrab; Rokhsarpour, Hamed; Shoja, Sara; Gholizadeh, Mostafa; Rahmatabad, Mohammad Ali Dashti; de Brito, Jorge (Construction & building materials, 2020)
•Using magnetized water leads to a higher slump flow and a lower viscosity of the SCC mixes;•Magnetized water significantly improved the mechanical properties of the SCC mixes;•The improvement depends on the number of times that water passes through the permanent magnetic field;•The addition of steel fibres to the SCC mixes significantly improved their hardened properties;•Multi-expression programming was successfully employed to generate describing models. The objective of this research is to investigate the effect of magnetized water on the fresh and hardened properties of self-compacting concrete (SCC) reinforced with different ratios of steel fibres. For this purpose, a total of 12 mixes were produced with different contents of steel fibres (0%, 0.35%, 1%, and 1.65% by volume of concrete) and the mixing water passed through a permanent magnetic field (with a strength of 0.65 T), 1 and 15 times, at a flow speed of 0.75 m/s. Slump flow, V-funnel, compressive strength, splitting tensile strength and flexural strength tests, as well as a statistical analysis, were conducted. The results of the workability, compressive strength, splitting tensile strength and flexural strength tests indicate that the SCC mixes are considerably enhanced by magnetizing the mixing water. Finally, a novel evolutionary programming technique called multi-expression programming was used to generate mathematical models.